Technical paper effect of cement and water cement ratio on sand rbick using poc. - Sahal Ahmed Sugule (School of Environmental Engineering, University Malaysia Perlis, 2014)
This paper investigates the principle effects of cement and water cement ratio on sand brick and bricks having Palm Oil Clinker used as replacement of fine sand aggregates. Palm oil clinker is attained from milling process of Palm oil. The used of POC aggregates as alternative of natural sand aggregates in the construction purpose is important for much reason. If the Palm oil is used for construction purposes will solve the problems of disposal solid waste into the environment and the second most important advantage is the reducing of high consumption of natural aggregates.